Recipes for Commonly Encountered Reagents. Issue 17 (21st September 2018) - Gallagher, Sean R.
Abstract: This unit lists recipes for many of the buffers and other reagents typically found in a molecular biology laboratory. For reagents specific to a given technique, refer to the unit describing the method. © 2018 by John Wiley & Sons, Inc.